European cities in the knowledge-based economy: Observations and policy challenges. - Winden, Willem van (TH Zürich, NSL, 2009)
Der Beitrag untersucht neue Herausforderungen für stadtbezogene Governanceformen aus der Perspektive der wissensbasierten Ökonomie-Formen. Dabei interessieren insbesondere drei Aspekte: Die ungleiche Verteilung von wissensinduziertem Wirtschaftswachstum in europäischen Städten, die Frage einer möglichen aufholenden Entwicklung in den zurückgebliebenen Städten und Regionen durch die Wissensindustrie oder eines weiteren Auseinandergehens der Entwicklungsschere sowie drittens die Rolle akademischer Ausbildungsstätten in den Städten. Es wird auch der Frage nachgegangen, ob Technologie- und Wissenschaftsparks als Netzwerke kleiner und großer Unternehmen planbar sind und sich kreative Milieus ansiedeln lassen.

The essay discusses a set of related issues concerning the urban transition towards a knowledge-based economy. First, it deals with the uneven distribution of economic growth among various types of cities in the knowledge-based economy; second, it reflects on emerging economic and social divisions within cities. Does the knowledge economy offer opportunities to repair these social and economic divides or does it deepen them instead? Third, we deal with the alleged new role of institutions of higher education (HEIs). Cities increasingly consider them to be engines of growth in the urban knowledge economy, but is this borne out by reality? Our final topic is concerned with urban planning. Many European cities try to create "knowledge locations", aiming to promote innovation and creativity in those areas and/or increase the value of the real estate. We add some critical reflections.
Keywords: Wirtschaftsentwicklung; Wirtschaftswachstum; Standort; Innovation; Wirtschaftsförderung; Technologiepark; Technologiepolitik; Wissenschaft; Forschung; Kooperation; Local Governance; Standortförderung; Hochtechnologie; Wissensmilieu; Kreatives Milieu; Netzwerk